Review: Political Legitimacy and Underrepresentation: How Do Citizens Evaluate the Political System? (PhD by David Talukder, Université Libre de Bruxelles) - Foa, Roberto (Politics of the Low Countries, 2025)
By filling this gap, David Talukder’s doctoral dissertation, Political Legitimacy and Underrepresentation, offers a valuable contribution to the literature. In his study, Talukder goes beyond generic assessments of democracy in order to examine specific facets of its functioning, such as whether respondents feel their views are represented politically, whether the democratic process is perceived as efficient, and whether citizens are satisfied with the resultant policy outcomes. Applying Vivien Schmidt’s threefold subdivision of democratic legitimacy into input, throughput and output components – that is, the degree of citizen satisfaction with how their preferences are represented, how policy is made and, finally, with the policies themselves – Talukder helps us to better understand the bases of contemporary democratic discontent. As a result, a clear strength of this thesis is the care and attention that is given to the task of conceptualising political legitimacy and operationalising each element of this framework with appropriately chosen survey indicators.